Physics of environmental flows interacting with obstacles - Zhou, Jian, author; Venayagamoorthy, Subhas K., advisor; Julien, Pierre Y., committee member; Bledsoe, Brian P., committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2017)
The effects of natural and man-made obstacles on their surrounding environmental flows such as rivers, lakes, estuaries, oceans and the atmosphere has been the subject of numerous studies for many decades. The flow-obstacle interaction can lead to the generation of turbulence which determines local flow dynamics and even large-scale circulations. The characteristic chaotic and enhanced mixing properties of turbulence in conjunction with other environmental conditions such as the clustering of multiple obstacles and density variations raise a number of interesting problems pertaining to both fundamental fluid dynamics and practical engineering applications. Insights into these processes is of fundamental importance for many applications, such as determining the fate of deep water-masses formed in the abyssal ocean, optimizing the productivity and environmental impact of marine farms, predicting the amount of power that a group of turbines can generate, estimating carbon dioxide exchange between the forests and the atmosphere or modeling flood routing in vegetated rivers. The main aim of this dissertation is to use high-resolution numerical simulations to study environmental flows of different forcing mechanisms interacting with obstacles of different geometries. The objectives are multi-fold: (i) To gain insights into the three-dimensional hydrodynamics of constant-density flows interacting with a finite canopy; (ii) To develop an unambiguous geometrical framework for characterizing canopy planar geometry; (iii) To explore the fundamental differences in the flow dynamics between porous canopies and their solid counterpart; and (iv) To investigate the effect of ambient density stratification on flow-obstacle interactions. The first part of this dissertation focuses on the mean three-dimensional hydrodynamics in the vicinity of a suspended cylindrical canopy patch with a bulk diameter of D. The patch was made of Nc constituent solid circular cylinders with h in height and d in diameter, and was suspended in deep water (H/h ≫ 1 where H is the total flow depth). After the validation against published experimental data, large eddy simulations (LES) were conducted to study the effects of patch density (0.16 ≤ φ = Nc(d/D)2 ≤ 1, by varying Nc) and patch aspect ratio (0.25 ≤ AR = h/D ≤ 1, by varying h) on the near-field flow properties. It was observed qualitatively and quantitatively that an increase in either φ or AR decreases bleeding velocity along the streamwise direction but increases bleeding velocities along the lateral and vertical directions, respectively. A close examination at the flow inside the patch reveals that despite the similar dependence of vertical bleeding on φ and AR, the underlying physics are different. However, in contrast to the bleeding velocity, a flow-rate budget shows that the proportion of the vertical bleeding flow leaving the patch with respect to the total flow entering the patch (i.e. relative vertical bleeding) decreases with increasing AR. Finally, the interlinks between patch geometry, flow bleeding and flow diversion are identified: the patch influences the flow diversion not only directly by its real geometrical dimensions, but also indirectly by modifying flow bleeding which enlarges the size of the near-wake. While loss of flow penetrating the patch increases monotonically with increasing φ, its partition into flow diversion around and beneath the patch shows a non-monotonic dependence, highlighting the fundamental differences in the flow dynamics between porous patches and their solid counterpart. Next, the propagation of full-depth lock-exchange bottom gravity currents over a submerged array of circular cylinders is investigated using laboratory experiments and LES. Firstly, to investigate the front velocity of gravity currents across the whole range of array density φ, the array is densified from a flat-bed (φ = 0) towards a solid-slab (φ = 1) under a particular submergence ratio H/h, where H is the flow depth and h is the array height. The time-averaged front velocity in the slumping phase of the gravity current is found to first decrease and then increase with increasing φ. Next, a new geometrical framework consisting of a streamwise array density μx = d/sx and a spanwise array density μy = d/sy is proposed to account for organized but nonequidistant arrays (μx 6 ≠ μy), where sx and sy are the streamwise and spanwise cylinder spacings, respectively, and d is the cylinder diameter. It is argued that this two-dimensional parameter space can provide a more quantitative and unambiguous description of the current-array interaction compared with the array density given by φ = (π/4) μxμy. Both in-line and staggered arrays are investigated. Four dynamically different flow regimes are identified: (i) through-flow propagating in the array interior subject to individual cylinder wakes (μx: small for in-line array and arbitrary for staggered array; μy: small); (ii) over-flow propagating on the top of the array subject to vertical convective instability (μx: large; μy: large); (iii) plunging-flow climbing sparse close-to-impermeable rows of cylinders with minor streamwise intrusion (μx: small; μy: large); and (iv) skimming-flow channelized by an in-line array into several sub-currents with strong wake sheltering (μx: large; μy: small).Finally, the flow dynamics of intrusive gravity currents past a bottom-mounted obstacle in a continuously stratified ambient was numerically investigated, highlighting the effect of ambient stratification which is not considered in the previous sections. The propagation dynamics of a classic intrusive gravity current was first simulated in order to validate the numerical model with previous laboratory experiments. A bottom-mounted obstacle with a varying non-dimensional height of ˜D = D/H, where D is the obstacle height and H is the total flow depth, was then added to the problem in order to study the downstream flow pattern of the intrusive gravity current. For short obstacles, the intrusion re-established itself downstream without much distortion. However, for tall obstacles, the downstream flow was found to be a joint effect of horizontal advection, overshoot-spring back phenomenon, and associated Kelvin-Helmholtz instabilities. Analysis of the numerical results show that the relationship between the downstream propagation speed and the obstacle height can be subdivided into three regimes: a retarding regime (˜D ≈ 0 ∼ 0.3), an impounding regime (˜D ≈ 0.3 ∼ 0.6), and a choking regime (˜D ≈ 0.6 ∼ 1.0).Overall, at a fundamental level, this dissertation aims to contribute to an improved understanding of the physics associated with environmental flows interacting with obstacles. Moreover, the results from this research are expected to facilitate better parameterizations of this important class of flows.
Keywords: environmental fluid mechanics; fluid mechanics; hydraulics; flow-structure interaction; canopy flows; gravity current